2011
DOI: 10.1051/0004-6361/201014891
|View full text |Cite
|
Sign up to set email alerts
|

STIS optical spectroscopy of the lobes of CRL 618

Abstract: Context. Many proto-planetary nebulae show collimated structures sometimes showing multiple outflows. Aims. We present the results of new optical spectroscopic observations (both medium (with a dispersion of 0.56 Å pixel −1 ) and low (2.73 and 4.92 Å pixel −1 for the G430L and G750L gratings) spectral resolution) of the lobes of the proto-planetary nebula CRL 618 obtained with the Space Telescope Imaging Spectrograph on board of the Hubble Space Telescope. Methods. We analyse the density structure and the exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Haro-Corzo et al (2009) analyzed the influence of the orbital motion on the optical emission of these objects, by means of 3D hydrodynamical simulations. Their predicted [N ii] emission line maps can produce different luminosities for the two lobes, as observed in CRL 618 (Sánchez Contreras et al 2002;Riera et al 2011). …”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Haro-Corzo et al (2009) analyzed the influence of the orbital motion on the optical emission of these objects, by means of 3D hydrodynamical simulations. Their predicted [N ii] emission line maps can produce different luminosities for the two lobes, as observed in CRL 618 (Sánchez Contreras et al 2002;Riera et al 2011). …”
Section: Introductionmentioning
confidence: 86%
“…Unfortunately, the slit was displaced A&A 561, A145 (2014) from the leading bow-shocks. Comparing the observations with plane-parallel shock models, Riera et al (2011) found that the shock velocities lie in a narrow range between 30 and 40 km s −1 , except for the [O iii]/Hβ line ratios which require higher shock velocities (80-90 km s −1 ). The predicted shock velocities are significantly lower than the velocities with which the jets move outward.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Figure 6 displays position-velocity (PV) diagrams (bottom panels) for model M1 (xz projection) considering both orientations with respect to the plane of the sky. As in Figure 3 of Riera et al (2011), the PV diagrams display several ramps in radial velocity. This is clearly shown in the enlargement (upper panel) of the white rectangular region in the left panel.…”
Section: Proper Motions and Position-velocity Diagrammentioning
confidence: 86%